Evaluate dual forage and grain productivity of some cereal winter crops under different nitrogen fertilization levels - Saad, A. M. (2015)
This study was designed and implemented to evaluate productivity of three cereal crops i.e. Wheat, Barley and Triticale as affected by different nitrogen levels i.e. 0, 100 and 200 kg N/fed, two field experiments were carried at Exp. Res. Sta., Fac. Agric., Benha Univ. during 201012011 and 2011/2012 seasons. Results indicated significant differences in the total fresh forage yield for each of the three crops under study. Highest fresh and dry forage yield was produced from Barley whereas, the lowest yield was obtained from wheat with significant differences of different magnitudes. Highest grain yield and yield component was recorded from sown triticale and the lowest was recorded from sown Barley with significant differences. It could be concluded that total forage and grain yield as well as yield components were substantially increased as nitrogen fertilization levels increased from 0 to 100 and up to 200kg N/fed, respectively. However, an opposite trend was observed for the No of spikelets/spike and spike length.
Includes references.
Summary in Arabic.
1
Keywords: Forage plants -- Fertilizers; Grain -- Fertilizers; Forage plants -- Production; Grain -- Production